Willingness To Pay For Sustainably Produced Beef: A Study on Urban Consumer Preferences - Widiarta, I Putu Gede Didik; Putri, Budi Rahayu Tanama; Qamara, Cori; Hellyward, James; Wijakesuma, Made Hardinata (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
The increasing environmental and ethical challenges associated with conventional beef production have intensified consumer awareness of sustainable food systems, particularly in urban areas of Indonesia. This study examines urban consumers’ willingness to pay (WTP) for sustainably produced beef, focusing on how sustainability attributes, including eco-certification, animal welfare, and environmental sustainability, affect purchasing decisions. Data were collected through a mixed-methods approach, integrating online surveys and Discrete Choice Experiments (DCE), involving a representative sample from five major urban centers: Jakarta, Surabaya, Padang, Balikpapan, and Denpasar. The findings indicate that eco-certification is the most valued attribute, with a marginal willingness to pay (MWTP) of IDR 25,000 per kilogram, followed by animal welfare (IDR 18,500) and environmental sustainability (IDR 15,000). Consumers also demonstrated a general willingness to pay a 20% premium for sustainably produced beef, although regional disparities were observed. Jakarta and Surabaya exhibited the highest WTP premiums, at 23% and 22%, respectively, reflecting the influence of socioeconomic variables, including income, educational attainment, and environmental awareness. These results underscore the growing importance of environmental concerns and ethical considerations in shaping urban consumers’ preferences for beef products. The study contributes to the limited body of literature on sustainable meat consumption behavior in emerging markets, offering practical insights for policymakers, producers, and marketers in designing targeted strategies to promote sustainable beef consumption and support the development of environmentally responsible livestock industries in Indonesia.